Supporting And Obstacling Factors In The Pattern Partnership - Kusumawardana, Andhika; Usrotin Choiriyah, Ilmi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine how the supporting and inhibiting factors in the partnership pattern of the Pari temple tourism object. This research is a descriptive qualitative research with the technique of determining the informants using purposive sampling. In this study, the informants were the head of the Destinations and Tourism Marketing division, as well as employees of the tourism sector. The location of this research was conducted in Candi Pari Village, Porong District, Sidoarjo Regency. The data collection techniques were interviews, observations, documentation and literature studies. Data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the supporting and inhibiting factors in the development of the Pari temple tourism object are land acquisition and participation for the supporting factor, while the inhibiting factors for the Institutional, Outside and Resident Partnership Pattern to Increase Pari Temple tourism are, among others, limited land and location conditions.